2020
DOI: 10.31969/alq.v26i1.827
|View full text |Cite
|
Sign up to set email alerts
|

Problematika Pembelajaran Kitab Kuning Di Pesantren Putra Alkhairaat Pusat Palu

Abstract: <p>Kitab Kuning merupakan salah satu rukun dari beberapa rukun pesantren. Oleh karena itu, pembelajaran Kitab Kuning sesuatu yang mutlak dilaksanakan oleh setiap pesantren. Namun faktanya, banyak pesantren yang tidak melaksanakan pembelajaran kitab Kuning. Penelitian ini merupakan penelitian kualitatif deskriptif yang memotret problem pembelajaran kitab kuning yang dihadapi oleh Pesantren Putra Alkhairaat Pusat Palu. Kajian ini menemukan bahwa Kitab Kuning diajarkan secara langsung di Pesantren P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
1
3
0
2
Order By: Relevance
“…Furthermore, that most of these teachers do not emphasize the practice of I'rab learning on the subjects they teach, so if it is seen, the students feel that it is futile to learn I'rab tool knowledge while its application does not exist. This agrees with Amir (2020) that in terms of cadre, it offers a modern cadre system by referring to the stages: i) selection of potential cadres, ii) general and special education that supports the needs of cadres, iii) internship practices, iv) cadre certification to fulfill targets or no. For this reason, pesantren must develop a new function, namely the preparation of cadres as an effort to cooperate with other institutions (Rini et al, 2021).…”
Section: Teachers Problems In I'rab Learningsupporting
confidence: 88%
See 2 more Smart Citations
“…Furthermore, that most of these teachers do not emphasize the practice of I'rab learning on the subjects they teach, so if it is seen, the students feel that it is futile to learn I'rab tool knowledge while its application does not exist. This agrees with Amir (2020) that in terms of cadre, it offers a modern cadre system by referring to the stages: i) selection of potential cadres, ii) general and special education that supports the needs of cadres, iii) internship practices, iv) cadre certification to fulfill targets or no. For this reason, pesantren must develop a new function, namely the preparation of cadres as an effort to cooperate with other institutions (Rini et al, 2021).…”
Section: Teachers Problems In I'rab Learningsupporting
confidence: 88%
“…The use of the Amtsilati method in Qawa'id Learning (Nahwu and Sharaf) at Islamic Boarding Schools (Nurohmah, 2019;Ainifarista, 2018); Ikhtilaf Al-I'rab in the Al-Quran Surah Al-Insan and its implications in learning Nahwu at Madrasah Tsanawiyah (Mu'min, 2021); The problems and strategies of learning the Yellow Book (Amir, 2020;Wahyuno, 2019; The Existence of Pesantren, Kiai and Kitab Kuning learning as the main element of Islamic education in Indonesia (Zulmuqim, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Apalagi di lembaga-lembaga pembelajaran Islam yang diucap pesantren Alquran sekalipun. Pembelajaran serta pengajarannya lebih ditekankan pada upaya penghafalan serta pelatihan metode membaca serta melagukan Alquran, bukan pada upaya uraian serta pengkajian Alquran dalam pengertiannya yang luas (Amir, 2020;Sulthon & Khusnuridlo, 2006).…”
Section: Budaya Pesantrenunclassified
“…The research gaps from this study can be seen from several relevant studies that have been carried out by previous researchers, namely Amir's research stating that the method used at the Pesantren seems to be the same as other combination boarding schools that open school/madrasah education units, namely using the classical system. However, they also do not ignore the traditional method of halaqah in the mosque which is actually considered easier to provide religious understanding to students from studying the book (Amir, 2020). The results of Sarihat et al's research found that the teacher has attempted the availability of facilities in this Kitab kuning learning, right before using the online system or after using it (Sarihat et al, 2020).…”
Section: Introductionmentioning
confidence: 99%